2017
DOI: 10.1186/s12885-017-3859-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical trial of a novel autologous modified-DC vaccine in patients with resected NSCLC

Abstract: BackgroundThe primary aim of this study was to evaluate the safety of a novel dendritic cell (DC) vaccine pulsed with survivin and MUC1, silenced with suppressor of cytokine signaling 1 (SOCS1), and immune stimulated with flagellin for patients with stage I to IIIA non-small cell lung cancer (NSCLC) in a phase I open-label, uncontrolled, and dose-escalation trial. Moreover, we evaluate the potential efficacy of this modified DC vaccine as secondary aim.MethodsThe patients were treated with the vaccine at 1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 64 publications
0
25
1
Order By: Relevance
“…Additionally, suppressor of cytokine signal 1 (SOCS1) [106] was also used in this system due to its essential role in negative regulation of DC differentiation and antigen presentation. After DC vaccine treatment, the expression of tumor markers was significantly reduced and the living quality of all patients was improved [107]. In another clinical trial, DCs were transduced with an adenoviral vector expressing C–C motif chemokine ligand 21 (CCL21), which attracts DCs and T cells by interacting with C–C motif chemokine receptor 7 (CCR7) and C-X-C motif chemokine receptor 3 (CXCR3) receptors, recruits antigen-stimulated DCs into T-cell zones in secondary lymphoid organs, and plays a key role in T-cell activation.…”
Section: Progress In the Clinical Application Of DC Function Restorationmentioning
confidence: 99%
“…Additionally, suppressor of cytokine signal 1 (SOCS1) [106] was also used in this system due to its essential role in negative regulation of DC differentiation and antigen presentation. After DC vaccine treatment, the expression of tumor markers was significantly reduced and the living quality of all patients was improved [107]. In another clinical trial, DCs were transduced with an adenoviral vector expressing C–C motif chemokine ligand 21 (CCL21), which attracts DCs and T cells by interacting with C–C motif chemokine receptor 7 (CCR7) and C-X-C motif chemokine receptor 3 (CXCR3) receptors, recruits antigen-stimulated DCs into T-cell zones in secondary lymphoid organs, and plays a key role in T-cell activation.…”
Section: Progress In the Clinical Application Of DC Function Restorationmentioning
confidence: 99%
“…g ., mutated neoantigens, cancer germline proteins, and viral proteins) and tumor-associated antigens (TAAs) that are encoded by tissue-specific genes but over-expressed in tumor cells These antigens are loaded on DCs in the form of synthetic peptides, tumor-derived exosomes, autologous or allogeneic cell lysates from killed tumor cells or immunogenic cell death, or by transfecting DCs with tumor-derived whole RNA or DNA [47]. Presently, a limited repertoire of cancer antigens for DC loading has been identified to be immunogenically efficient that could elicit an immune response and result in tumor eradication, such as MAGE antigens, gp100, α-fetoprotein (AFP), glypican-3 (GPC-3), Wilms tumor 1, NY-ESO-1, MUC1, and mutated neoantigens [1, 4, 8]. In addition, DC adjuvants are also key to induce DC maturation and activation and, thus, intensify the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…LPS-activated DCs also synergized with PD-1 therapy and were substantially safer. DC immunotherapy has been used previously in clinical trials to revert CD8 T cell exhaustion, but it has not shown significant clinical benefits [4649]. Our studies are novel, because we show for the first time that DC immunotherapy using LPS-activated DCs improves the efficacy of PD-1 therapy.…”
Section: Discussionmentioning
confidence: 82%